Limitations on Freedom of Religion and Belief in the Jurisprudence of the European Court of Human Rights in the Quarter Century since Its Judgment in Kokkinakis v. Greece - Hill, Mark (Religion and human rights, 2017)
The manifestation of religious beliefs under Article 9 the European Convention on Human Rights is not absolute but may be subject to prescribed limitations. This article discusses the nature and extent of those limitations, as interpreted in the case law of the European Court of Human Rights from its decision in Kokkinakis v. Greece up to the present. It contrasts the prescriptive text of the Article with its lose and inconsistent interpretation by the Court in Strasbourg. Particular attention is given to the criteria of “prescribed by law”, “necessary in a democratic society”, “public safety”, “public order, health or morals” and “the rights and freedoms of others”. It seeks to divine principles from the varied jurisprudence, particularly at its intersection with the Court’s illusory doctrine of margin of appreciation.